Krisis Pendidikan Islam pada Generasi Muda di Perkebunan Tanjung Beringin - Husein, Ismail; Syari, Isma Aulia Zamaakh; Khairina, Khairina; Sinaga, Husnia Amro Br; Pane, Maahfuzha (Institut Agama Islam Sunan Giri Ponorogo, 2025)
The young generation growing up in this area often has limited access to quality education, especially religious education. This phenomenon is a serious problem in various regions including North Sumatra. The purpose of this study was to analyze the crisis of Islamic education in the young generation that occurred in Tanjung Beringin Plantation Village. The research method uses a qualitative descriptive approach, the analysis used is interactive data analysis with stages of data collection, data reduction, data presentation, and drawing conclusions. The data sources used in this study were obtained from primary data sources through interviews and secondary data obtained from books and journals related to the discussion. The results of the study showed that several results were found, including: Lack of educators, The importance of government support, The unavailability of non-formal Islamic educational institutions, Lack of parental roles. The solution that can be given to overcome some of the above is to provide non-formal Islamic religious education institutions that are complete with various facilities and teachers who have abilities in the field of religion.